2017
DOI: 10.18533/ijbsr.v6i11.1022
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Styles, Organisational Culture and Learning Organisational Capability in Education Industry: Evidence from Egypt

Abstract: <p>We aim in this study to explore the interaction between three constructs: leadership style, organisational culture, and organisational learning capacity.  In addition to that, we investigated the validity of this trio relationship in both public and private Egyptian universities situated in Greater Cairo area. A quota sampling procedure was used to recruit 298 academicians - 186 from public universities and 112 from private universities. Significant correlations were obtained between transformational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Alsabbagh and Khalil (2017) also found a negative correlation between organizational learning and hierarchy culture. Dajani and Mohamad (2017) were unable to find any significant relationship between hierarchy culture and organizational learning capability. This suggests there is controversy in the results of previous studies, and investigating motivation is essential.…”
Section: Clan Culture and Organizational Learningmentioning
confidence: 77%
See 2 more Smart Citations
“…Alsabbagh and Khalil (2017) also found a negative correlation between organizational learning and hierarchy culture. Dajani and Mohamad (2017) were unable to find any significant relationship between hierarchy culture and organizational learning capability. This suggests there is controversy in the results of previous studies, and investigating motivation is essential.…”
Section: Clan Culture and Organizational Learningmentioning
confidence: 77%
“…Their study suggested that clan and adhocracy cultures were positively linked to organizational learning. Dajani and Mohamad (2017) found that clan, adhocracy and market cultures were significantly correlated with organizational learning capability. In another study, Oh and Han (2020) reported that clan culture had a positive relationship with organizational learning in Korean companies.…”
Section: Clan Culture and Organizational Learningmentioning
confidence: 95%
See 1 more Smart Citation
“…Various factors influence organizations' rate and quality of change, be it externally or internally (Rizescu & Tileaga, 2016). Others mentioned that institutional change leaders work within culture while challenging their comfort zone to create rooms to reform (Dajani & Mohamad, 2016). Taking into consideration, this paper aims to provide a better understanding of adapting the reform process, integrating the most pertinent factors into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Institutional change leaders work within culture while challenging their comfort zone to create reforms (Dajani & Mohamad, 2016;Leal Filho et al, 2018;Sporn, 1996). Schein (1996) mentioned that culture is influenced by the institutional environment and is learned over some time.…”
Section: Introductionmentioning
confidence: 99%